Security protocols XXIII : 23rd International Workshop, Cambridge, UK, March 31-April 2, 2015, revised selected papers /: 23rd International Workshop, Cambridge, UK, March 31-April 2, 2015, revised selected papers. (2015) - Unknown
No abstract available